2007
DOI: 10.1523/jneurosci.3516-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Brain Machine Interfaces for the Control of Movement

Abstract: Quite recently, it has become possible to use signals recorded simultaneously from large numbers of cortical neurons for real-time control. Such brain machine interfaces (BMIs) have allowed animal subjects and human patients to control the position of a computer cursor or robotic limb undertheguidanceofvisualfeedback.Althoughimpressive,suchapproachesessentiallyignorethedynamicsofthemusculoskeletalsystem,and they lack potentially critical somatosensory feedback. In this mini-symposium, we will initiate a discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…The field of BMIs is expanding rapidly, and a variety of methods for decoding cortical signals have been proposed. One method of obtaining a control signal for BMIs is to decode EMG signals from cortical recordings, and several groups are actively exploring this decoding paradigm (Fagg et al 2007;Nazarpour et al 2012;Pohlmeyer et al 2007;Santucci et al 2005). One advantage EMG decoding has over kinematic decoding is that EMG signals are related to movement dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field of BMIs is expanding rapidly, and a variety of methods for decoding cortical signals have been proposed. One method of obtaining a control signal for BMIs is to decode EMG signals from cortical recordings, and several groups are actively exploring this decoding paradigm (Fagg et al 2007;Nazarpour et al 2012;Pohlmeyer et al 2007;Santucci et al 2005). One advantage EMG decoding has over kinematic decoding is that EMG signals are related to movement dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Linear decoders are common, due to their simplicity and ease of use, as well as their effectiveness in extracting behavioral variables from neuronal activity (Lebedev et al 2008;Wessberg et al 2000). Linear algorithms applied to decoding EMG signals from cortical activity include the Wiener filter (Carmena et al 2003;Fitzsimmons et al 2009;Santucci et al 2005) and multiple input-single output systems (Pohlmeyer et al 2007), both of which make predictions based on a combination of weighted neural activity (Pohlmeyer et al 2007). Other approaches incorporate nonlinear elements, such as the Wiener cascade, which is a dynamic linear system that includes a fixed nonlinear element (Pohlmeyer et al 2009).…”
mentioning
confidence: 99%
“…Since then interest in prosthetic somatosensation has dramatically increased (Fagg et al, 2007). London and colleagues demonstrated that rhesus monkeys can be cued by patterns of ICMS applied to the area 3a subdivision of primary somatosensory cortex, an area that is generally believed to be involved in the processing of proprioception and kinesthesia.…”
Section: Prosthetic Somatosensationmentioning
confidence: 99%
“…These BMI systems translate brain signals into commands for controlling devices such as cursors [1], spelling devices [2], and neural prosthetics [3][4][5][6][7][8][9]. This new communication has not only the potential to help to disabled persons but also provide insight into the motor system of the brain [10][11][12][13][14].Several sensors have been developed to measure brain signals. These are mainly categorized into two types, invasive sensor i.e.…”
mentioning
confidence: 99%